GÉNERO Y DIFERENCIAS COGNITIVAS EN LA SOLUCIÓN DE PROBLEMAS DE RAZONAMIENTO ESPACIAL - Rubio S, Martha R. (Tecné, Episteme y Didaxis: TED, 2000)
This paper aims to present that cognitive differences in spatial reasoning are not only due to biological component (female or male genres), but also to the learning enviroment in which individuals are involved. This component affects deeply this kind of reasoning. The statistics analysis of data collected in this investigation by using a computer program “Play and discover: spatial reasoning and design”, concluded that when male and female individuals are engaged in reasoning problems under the same Iearning environments, efflcay and efficiency differences have a tendency fo diminish.